Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$ \sum^{n}_{k=1} k^3 = ({n^2(n+1)^2})/4 $$

right?

say for example k not equal to 1, why doesn't this work? I subtracted the summation of k-1? $$ \sum^{n}_{k!=1} k^3 = ({n^2(n+1)^2 - (k-1)^2k^2})/4 $$

share|improve this question
    
How does it not work? –  Karolis Juodelė Nov 12 '12 at 15:34
2  
Do you understand that $k$ is not a constant here, so it has no meaning outside the $\sum$? –  Thomas Andrews Nov 12 '12 at 15:34
    
I'm not quite sure what your question is here. What exactly are you trying to show? –  Michael Dyrud Nov 12 '12 at 15:34
1  
Your notation was meaningless - I had to ask several questions to figure out what you meant by your notation. $$\sum_{k\neq 1}^n$$ is not a valid mathematical formula (and there was no interpreation of it that gave me what you meanted to ask, since you meant $k=j$ or $k>j-1$ or some such.) –  Thomas Andrews Nov 12 '12 at 15:48
1  
Also, there is no way for $\sum_k$ to end up being a function of $k$ because $\sum_k$ is an expression that means as $k$ varies, so the right side can't have $k$ in it - there is no one value of $k$ to put on the right side. That was why I added the variable $j$ as the "starting point." –  Thomas Andrews Nov 12 '12 at 15:52

2 Answers 2

up vote 1 down vote accepted

Ignoring your title, if you are asking for $$\sum^{n}_{k=j} k^3 $$ (so starting at $j$ instead of $1$) you can write $$\sum^{n}_{k=j} k^3 = \sum^{n}_{k=1} k^3 -\sum^{j-1}_{k=1} k^3=({n^2(n+1)^2})/4-(j^2(j-1)^2)/4$$

share|improve this answer
    
Beat me to it :) –  Greg Ros Nov 12 '12 at 16:05

I'll try to answer the question as best I can. For any sum, the following identity holds, where $n > m > a$:

$$\sum_{k=a}^{n}{f(k)}=\sum_{k=a}^{m}{f(k)}+\sum_{k=m+1}^{n}{f(k)}$$

From this, we can note and conclude, via substitutions:

$$\sum_{k=a}^{n}{f(k - b)}=\sum_{k=a-b}^{n-b}{f(k)}$$ So: $$\sum_{k=b}^{n}{f(k)}=\sum_{k=a}^{n}{f(k)}-\sum_{k=a}^{b-1}{f(k)}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.